2013
DOI: 10.4028/www.scientific.net/amr.734-737.1086
|View full text |Cite
|
Sign up to set email alerts
|

Study on Collector for Reverse Flotation of Certain Phosphorite in Guizhou

Abstract: On the basis of the contrastive research into the flotation performance of several vegetable oil fatty acids, the rapeseed oil fatty acid with better performance was screened out from many fatty acids, and its linolenic acid C18:3content is15.81%, then through modifying and compounding, new magnesium removal collector EM-LS-01was obtained. With the use of this agent in certain low-grade high-Mg phosphorite, the phosphate concentrate indexes of single reverse flotation are grade of 30.25% P2O5, recovery of 90.6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…The physical and chemical properties of the mineral surface have a significant influence on the adsorption of the collector on the mineral surface, so the selection of the appropriate collector can enhance the flotation efficiency to a large extent. Fatty acids are conventional collectors used for the flotation of apatite (Li et al, 2013;Cao et al, 2016) because of their high affinity as well as a low cost (Ruan et al, 2017, Wang et al, 2019. Liu et al (2017) reported that saponified fatty acid was used as collector, which made apatite easier to float by combining with Ca 2+ active sites on apatite surface.…”
Section: Introductionmentioning
confidence: 99%
“…The physical and chemical properties of the mineral surface have a significant influence on the adsorption of the collector on the mineral surface, so the selection of the appropriate collector can enhance the flotation efficiency to a large extent. Fatty acids are conventional collectors used for the flotation of apatite (Li et al, 2013;Cao et al, 2016) because of their high affinity as well as a low cost (Ruan et al, 2017, Wang et al, 2019. Liu et al (2017) reported that saponified fatty acid was used as collector, which made apatite easier to float by combining with Ca 2+ active sites on apatite surface.…”
Section: Introductionmentioning
confidence: 99%